Five phase space vector modulation voltage source inverter using large vector only / Mohd Syazimie Zulkifli - Zulkifli, Mohd Syazimie (2012)
AC machine with a phase number higher than three enables utilization in electric drives and considered for several applications today. The multi-phase gives more advantages compared to three-phase counterparts. Furthermore, devising appropriate control algorithm is also important while modeling of Voltage Source Inverter (VSI). Besides, space vector is used as the method that preferred real-time modulation techniques and widely use for digital control of VSI. Since then, the study on Five Phase Space Vector Modulation (SVM) and VSI using large vector has been developed. However, this study concentrate on the outer most decagon space vector only that does not include the whole of the decagon, d-q plane. Furthermore, this study does not include the zero vectors at the time switching and only active vector were used for the time switching for each sector. The waveform of Line to Line Voltage, Phase to Neutral Voltage and Pole Voltage has been compared between theoretical waveform that has been calculated from Microsoft Excel and validate through simulation using MATLAB/Simulink. The Total Harmonic Distortion (THD) is compared with different modulation index and showed that the THD percentages reduced when the modulation index increased.